Database encryption system (CryptDB) establishment and gui development - Huang, Hao. (2012)
eXACML is new framework for sharing data on the could. Current design of eXACML framework is based on an assumption that cloud severs and the proxy server are honest, therefore data security at server end is not guaranteed. CryptDB is a system that provides practical and provable confidentiality in the face of attacks for applications backed by SQL databases. It is worthwhile to explore the potential to deploy CryptDB’s data encryption mechanism in eXACML.